Das europäische Navigationssatellitensystem 'Galileo': Herausforderungen und Perspektiven - Markus C. Kerber (Wirtschaftsdienst, 2015)
Mit dem Ziel, neben den bestehenden ein eigenes europäisches Navigationssatellitensystem zu etablieren, hat sich die Europäische Union eine große Aufgabe gestellt. Das umfangreiche industrielle Beschaffungsprojekt stößt an viele vergaberechtliche und -politische Grenzen. Die Bestandsaufnahme bei der Beschaffungsproblematik und die Entwicklungsperspektiven des Galileo-Betriebs sind Gegenstand dieses Beitrags. – – Apart from the contested institutional competence of the EU for the construction and management of a navigation satellite system the hitherto experience in the trial and validation phase has confirmed doubts concerning the EU's capacity to procure and manage an infrastructure like Galileo. Regarding the unresolved problems of maintenance and management, the concepts proposed by the EU regulation as of 11 December 2013 will not be sufficient to overcome the expected difficulties. With regard to the capacity of the EU as the owner of the Galileo navigation satellite system the question of whether to give a concession to an industrial consortium or to European industrial intermediaries is therefore more topical than ever.
Keywords: K00; L52; 330; Satellitenkommunikation; Öffentlicher Auftrag; EU-Staaten